Discrete differential geometry driven methods for architectural geometry - Yao, Sidan (Nanyang Technological University, 2022)
With the rapid growth of free form architectures, the demand for architectural geometry technologies increases dramatically in recent years. Architectural geometry contains knowledge highly relevant to computer graphics and geometry especially discrete differential geometry. In addition, architectural geometry provides new context for some well-established concepts and brings new challenges and new objectives. In this dissertation, we tackle four challenges in architectural geometry. These four proposed solutions cover various processes including architecture maintenance, architecture construction, architecture texture mapping and architecture decoration.